KAJIAN ARSITEKTUR POHON DALAM UPAYA KONSERVASI AIR DAN TANAH: STUDI KASUS ALTINGIAEXCELSA DAN SCHIMA WALLICHII DI TAMAN NASIONAL G. GEDE PANGRANGO - Nuraeni, Eni; Setiadi, Dede; Widyatmoko, Didik (Perhimpunan Biologi Indonesia, 2014)
Tree architectural model is basically a tree construction as a result of meristematic growth pattern. Tree architectureis closely associated with water and soil components, i.e. rainfall, throughfall, stem flow, infiltration, surface run-off,and erosion. For Altingia excelsa (Rasamala) plots, the results showed that the daily average of the rainfall intensityobserved was 9.67 mm, stem flow 0.03 mm, canopy throughfall 5.43 mm, infiltration 0.51 ml/mm2/second,surface run-off 3.45 mm, and erosion 5.66 kg/m2. For Schima wallichii (Puspa), the daily average of rainfall was9.67 mm, stem flow 0.04 mm, canopy throughfall 4.02 mm, infiltration 0.49 ml/mm2/second, surface run-off 8.18mm, and erosion 12.71 kg/m2. Compared to A. excelsa, S. wallichii significantly had larger values in someparameters measured, i.e. stem flow, surface run-off, and erosion, indicating that on land sopes of 70% of theMount Gede Pangrango National Park, individual plants of S. wallichii seemed to be well adapted. However,individuals of A. excelsa possessed a more spreadly branching model, larger vertical width, denser canopy, andskewed bark channels capable for slowing down the stem flow and canopy throughfall. Consequently plants of A.excelsa would generally be able to hold and conserve water and soil better than S. wallichii plants.Keywords: Tree architectural model, stem flow, throughfall, surface run-off, infiltration, erosion